2008
DOI: 10.3133/sir20085038
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for design and sampling for cyanobacterial toxin and taste-and-odor studies in lakes and reservoirs

Abstract: Temperature in degrees Fahrenheit (°F) may be converted to degrees Celsius (°C) as follows:°C =(°F-32)/1.8 Temperature in degrees Celsius (°C) may be converted to degrees Fahrenheit (°F) as follows:°F =(1.8×°C)+32.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 68 publications
0
31
0
2
Order By: Relevance
“…Monitoring and management programs are usually more systematic in high risk source waters, and increasingly, include cyanotoxins (e.g. Graham et al, 2008Graham et al, , 2012Hobson et al, 2010). In South Australian reservoirs, for example, the planktonic odor and toxin producing cyanobacterium Dolichospermum circinale is most likely to cause T&O issues during the warmer months from October to April, while in the River Murray, a lentic system, odorous planktonic populations of Dolichospermum, Pseudanabaena and Planktothrix can persist from summer into early winter under conditions of low flow and decreasing water temperatures.…”
Section: Monitoring and Managementmentioning
confidence: 98%
See 2 more Smart Citations
“…Monitoring and management programs are usually more systematic in high risk source waters, and increasingly, include cyanotoxins (e.g. Graham et al, 2008Graham et al, , 2012Hobson et al, 2010). In South Australian reservoirs, for example, the planktonic odor and toxin producing cyanobacterium Dolichospermum circinale is most likely to cause T&O issues during the warmer months from October to April, while in the River Murray, a lentic system, odorous planktonic populations of Dolichospermum, Pseudanabaena and Planktothrix can persist from summer into early winter under conditions of low flow and decreasing water temperatures.…”
Section: Monitoring and Managementmentioning
confidence: 98%
“…Modeling has also been used to predict T&O and relate outbreaks to environmental parameters and in some cases, cyanobacteria (Smith et al, 2002;Davies et al, 2004;Dzialowski et al, 2009;Graham et al, 2008;Parinet et al, 2013;Su et al, 2015;). Yet despite the substantial costs that cyanobacterialderived and other T&O events impart on drinking water and other industries, there are few guidelines or standards for acceptable odor levels in drinking water and this issue is most often managed in a reactive mode.…”
Section: Monitoring and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations suggest that picocyanobacterium Synechococcus sp. synthesize 2-methylisoborneol (MIB) and geosmin (1,2,7,7-tetramethyl-2-norbomeol) (GSM) [ 79 , 83 , 84 ]. It was also demonstrated that MIB is produced and secreted during cyanobacterial cell cycle, while GSM is released only after cells’ death.…”
Section: Picocyanobacterial Secondary Metabolitesmentioning
confidence: 99%
“…In a summary report for the 2008–2009 state legislature, the top three toxic cyanobacteria genera in Washington lakes were identified as Anabaena , Aphanizomenon , and Microcystis [ 69 ]. Gloeotrichia was also included because a recent study confirmed microcystin-LR production by Gloeotrichia echinulata [ 70 ], and exposure to this genus has led to reports of human health impacts in Washington lakes.…”
Section: Summary Of Freshwater Toxins Affecting Public Health In Wmentioning
confidence: 99%